Diary of a wimpy kid - the getaway - Kinney, Jeff (London Puffin, 2017)
In Diary of a Wimpy Kid: The Getaway, Greg Heffley and his family take a break from the winter cold by heading to a tropical island resort for a holiday getaway. Greg envisions a relaxing vacation filled with sunshine and fun, but things quickly go awry. From travel mishaps to unexpected encounters with wildlife and awkward social situations, the Heffleys find that paradise isn$1 (Bt all it$1 (Bs cracked up to be. Greg$1 (Bs dream vacation turns into a hilarious adventure filled with misfortune, family chaos, and plenty of laughs. As always, Greg records each twist and turn, giving readers a humorous glimpse into the highs and lows of family vacations.s